Synthesis, structure and properties of N-R-2-(5-(5-methyl-1H-pyrazole- 3-yl)-4-phenyl-4H-1,2,4-triazole-3-ylthio)acetamides - Hotsulia, A. S.; Fedotov, S. O. (Запорізький державний медичний університет, 2019)
Heterocyclic compounds remain the most promising group of compounds, through which the new drugs with characteristic list of properties are successfully created. Examples of this systems are 1,2,4-triazole and pyrazole. The presence in one molecule structure of fragments of two different azaheterocycles is synthetically interesting and allows increasing the probability to obtain biologically active substance with a wide spectrum of action. The aim of the work was to optimize the synthesis conditions and investigate the properties of N-R-2-(5-(5-methyl-1H-pyrazole-3-yl)-4- phenyl-4H-1,2,4-triazole-3-ylthio)acetamides in case of change of chemical process conditions. Methods and results. Ethyl 5-methyl-1H-pyrazole-3-carboxylate, which was obtained by known techniques using acetone, diethyl oxalate, sodium methoxide, followed by hydrazine hydrate in equivalent amount, was used as the key starting reagent. The resulting ethyl 5-methyl-1H-pyrazole-3-carboxylate was used to carry out hydrazinolysis reactions and nucleophilic addition of phenyl isothiocyanate with subsequent alkaline heterocyclicization. The synthesized 5-(5-methyl-1H-pyrazol-3-yl)-4-phenyl-4H-1,2,4-triazole-3-thiole was used in alkylation reactions with promising reagents for the design of pharmacophoric fragments. The products of such reaction are N-R-2- (5-(5-methyl-1H-pyrazole-3-yl)-4-phenyl-4H-1,2,4-triazole-3-ylthio)acetamides. The structure of the resulting compounds was confirmed by elemental analysis, 1H NMR spectroscopy, IR spectrophotometry. The individuality of the substances was determined by thin-layer chromatography and chromatographic mass spectrometry. For synthesized compounds, preliminary screening was performed using the PASS On-line® software and molecular docking. Conclusions. N-R-2-5-(5-methyl-1H-pyrazole-3-yl)-4-phenyl-4H-1,2,4-triazole-3-ylthio)acetamides are obtained with high yields and purity, their properties are investigated. Гетероциклічні сполуки залишаються найбільш перспективною групою, за їхньою допомогою відбувається успішне створення нових лікарських засобів із характерним переліком властивостей. Прикладами таких систем є 1,2,4-тріазол і піразол. Наявність у структурі однієї молекули фрагментів двох різних азагетероциклів є синтетично цікавим і дає змогу збільшити ймовірність одержання біологічно активної субстанції з широким спектром дії. Мета роботи – оптимізація умов синтезу та дослідження властивостей N-R-2-(5-(5-метил-1H-піразол-3-іл)-4-феніл-4H-1,2,4-тріа¬зол-3-ілтіо)ацетамідів при зміні умов перебігу хімічного процесу. Методи та результати. Як ключовий вихідний реагент використали етил 5-метил-1Н-піразол-3-карбоксилат, який одержали за відомими методиками з використанням ацетону, діетилоксалату, натрій метилату та з наступним використанням гідразин гідрату в еквівалентній кількості. Одержаний етил 5-метил-1Н-піразол-3-карбоксилат використали для реакцій гідразинолізу та нуклеофіль¬ного приєднання фенілізотіоціанату з наступною лужною гетероциклізацією. Синтезований 5-(5-метил-1Н-піразол-3-іл)-4-феніл- 4Н-1,2,4-тріазол-3-тіол використаний у реакціях алкілування перспективними реагентами для конструювання фармакофорних фрагментів. Продуктами такої реакції є N-R-2-(5-(5-метил-1H-піразол-3-іл)-4-феніл-4H-1,2,4-тріазол-3-ілтіо)ацетаміди. Структура одержаних сполук підтверджена за допомогою елементного аналізу, спектроскопії 1Н ЯМР, ІЧ-спектрофотометрії. Індивідуальність речовин встановлена за допомогою тонкошарової хроматографії та хромато-мас-спектрометрії. Для синтезованих сполук здійснили попередній розрахунковий скринінг за допомогою програмного продукту PASS On-line® та молекулярного докінгу. Висновки. Одержали з високими виходами та чистотою N-R-2-(5-(5-метил-1H-піразол-3-іл)-4-феніл-4H-1,2,4-тріазол-3-ілтіо) ацетаміди, доведели їхню структуру та дослідили властивості. Гетероциклические соединения остаются наиболее перспективной группой, с их помощью происходит успешное создание новых лекарственных средств с характерным перечнем свойств. Примеры таких систем – 1,2,4-триазол и пиразол. Наличие в структуре одной молекулы фрагментов двух разных азагетероциклов синтетически интересно и позволяет увеличить вероятность получения биологически активной субстанции с широким спектром действия. Цель работы – синтез и исследование свойств N-R-2-(5-(5-метил-1H-пиразол-3-ил)-4-феніл-4H-1,2,4-триазол-3-илтио)ацетамидов при изменении условий протекания химического процесса. Методы и результаты. В качестве ключевого исходного реагента использован этил 5-метил-1Н-пиразол-3-карбоксилат, который получен по известным методикам с использованием ацетона, диэтилоксалата, натрий метилата и с последующим использованием гидразин гидрата в эквивалентном количестве. Полученный этил 5-метил-1Н-пиразол-3-карбоксилат использован для проведения реакций гидразинолиза и нуклеофильного присоединения фенилизотиоцианата с последующей щелочной гетероциклизаци¬ей. Синтезированный 5-(5-метил-1Н-пиразол-3-ил)-4-фенил-4H-1,2,4-триазол-3-тиол использован в реакциях алкилирования перспективными реагентами для конструирования фармакофорных фрагментов. Продукты такой реакции – N-R-2-(5-(5-метил- 1H-пиразол-3-ил)-4-фенил-4H-1,2,4-триазол-3-илтио)ацетамиды. Структура полученных соединений подтверждена с помощью элементного анализа, спектроскопии 1Н ЯМР, ИК-спектрофотометрии. Индивидуальность веществ установлена с помощью тонкослойной хроматографии и хромато-масс-спектрометрии. Для синтезированных соединений проведен предварительный расчетный скрининг с помощью программного продукта PASS On-line® и молекулярного докинга. Выводы. Получены с высокими выходами и чистотой N-R-2-(5-(5-метил-1H-пиразол-3-ил)-4-феніл-4H-1,2,4-триазол-3-илтио) ацетамиды, доказана их структура и исследованы свойства.
Синтез, будова та властивості N-R-2-(5-(5-метил-1H-піразол-3-іл)-4-феніл-4H-1,2,4-тріазол-3-ілтіо)ацетамідів
Синтез, строение и свойства N-R-2-(5-(5-метил-1H-пиразол-3-ил)-4-феніл-4H-1,2,4-триазол-3-илтио)ацетамидов
Keywords: 2,4-тріазол; піразол; фізико-хімічні властивості; молекулярний докінг; 1,2,4-триазол; пиразол; физико-химические свойства; молекулярный докинг